2017
DOI: 10.4172/2376-127x.1000317
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorders during Pregnancy and Postpartum

Abstract: Pregnancy is the most beautiful and memorable time in a woman's life. Apart from medical and obstetrical challenges it involves a of lot emotional, psychological and social aspects too. Although women having medical and obstetrical disorders commonly seek treatment, psychological problems are often not addressed. A female may continue to live in a state of emotional turmoil and may attribute these changes to the hormonal changes in the body due to pregnancy. Psychiatric disorders which remain untreated can dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…An initial search identified 20,040 studies, of which, those with limited discussions in relation to MH outcomes and of poor quality, were excluded, resulting in a final dataset of 69 studies ( Table 1a ) of which 46 studies were systematically included and thematically analysed ( Table 2 ). These 46 studies included 26 qualitative [ 12 , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ], 17 cohort [ 7 , 18 , 21 , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] ], 6 controlled [61] , [62] , [63] , [64] , [65] , [66] , 2 randomised controlled trials [ 19 , 67 ] and 2 mixed methods [ 68 , 69 ] studies. Based on the eligibility criteria, and the quality assessment, 21 studies were selected for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An initial search identified 20,040 studies, of which, those with limited discussions in relation to MH outcomes and of poor quality, were excluded, resulting in a final dataset of 69 studies ( Table 1a ) of which 46 studies were systematically included and thematically analysed ( Table 2 ). These 46 studies included 26 qualitative [ 12 , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ], 17 cohort [ 7 , 18 , 21 , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] ], 6 controlled [61] , [62] , [63] , [64] , [65] , [66] , 2 randomised controlled trials [ 19 , 67 ] and 2 mixed methods [ 68 , 69 ] studies. Based on the eligibility criteria, and the quality assessment, 21 studies were selected for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 26 studies that reported psychological experiences of women with GDM [ 12 , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ], there appears to be psychological distress associated with concerns related to the baby [23] , blood glucose monitoring [45] and administering insulin injections [39] . Whilst these studies highlighted the emotional burden of GDM, the self-reported, subjective descriptions of the psychological distress experienced by these women, a clinical diagnosis remained absent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Untreated psychiatric disorders may interrupt social life and can have adverse effects on fetal and neonatal growth, so recognizing women at risk of developing psychiatric disorders during pregnancy and implementing timely management is essential [7].…”
Section: Introductionmentioning
confidence: 99%
“…Women during pregnancy experience variety of mental and physical disorders. For example, psychological issues including depression, obsessive compulsive disorder, anxiety, stress, panic disorder, mood disorders, sleep disorders, and psychological distress appeared to associated with pregnant women (Sharma, Singh, Tempe, & Malhotra, 2017). In particular, recent reviews reported that prevalence of depression (Woody, Ferrari, Siskind, Whiteford, & Harris, 2017) or disorders relating posttraumatic stress (Yildiz, Ayers, & Phillips, 2017) was 11.9% and 3.3 % among pregnant women, respectively.…”
Section: Introductionmentioning
confidence: 99%